2020
DOI: 10.1186/s13046-020-01659-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting NEK2 impairs oncogenesis and radioresistance via inhibiting the Wnt1/β-catenin signaling pathway in cervical cancer

Abstract: Background NEK2, a serine/threonine kinase involved in mitosis, has been found to function in chromosome instability, tumor progression and metastasis, but its role in cervical cancer radioresistance remains unknown. Methods We detected the protein levels of NEK2 in cervical carcinoma tissues and paired paracarcinoma tissues by immunohistochemistry. The roles of NEK2 in oncogenesis were examined using cell growth and colony formation assays, EdU assay, apoptosis assay as well as in vivo mouse model. γ-H2AX a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 43 publications
2
44
0
Order By: Relevance
“…In contrast, SOCS2 and DNASE1L3 were negatively related factors, which were associated with cell cycle regulation. Previous studies have pointed out that cell cycle alterations and mitosis signalling pathways are closely associated with cancer progression and affect cancer immune infiltration 47–49 . Recent studies have also suggested that complement cascade may be linked with tumour‐promoting inflammation and cancer immune infiltration 50 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, SOCS2 and DNASE1L3 were negatively related factors, which were associated with cell cycle regulation. Previous studies have pointed out that cell cycle alterations and mitosis signalling pathways are closely associated with cancer progression and affect cancer immune infiltration 47–49 . Recent studies have also suggested that complement cascade may be linked with tumour‐promoting inflammation and cancer immune infiltration 50 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have pointed out that cell cycle alterations and mitosis signalling pathways are closely associated with cancer progression and affect cancer immune infiltration. 47 , 48 , 49 Recent studies have also suggested that complement cascade may be linked with tumour‐promoting inflammation and cancer immune infiltration. 50 Thus, the target genes may contribute to the tumorigenesis and progression of HCC through promoting tumour cell proliferation and immune infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…The role of NEK2 in radioresistance was evaluated in HeLa, where NEK2 depleted cells show a significant increase in the tail comet and yH2AX foci formation, indicating that the NEK2 knockdown accelerates DNA damage [124].…”
Section: Nek2mentioning
confidence: 99%
“…Finally, the knockdown of NEK2 leads to negative regulation of WNT4/1, both on the mRNA and protein levels. This in turn leads to a down-regulation of beta-catenin and, consequently, to greater radioresistance and oncogenesis progression [124] (Figure 1).…”
Section: Nek2mentioning
confidence: 99%
“…The proteins mentioned above are also recognized as possible molecular targets in cancer. Indeed, knockdown or inhibition of PLK1 [77], CDK1 [78], AURKA [79], MELK [80,81], and NEK2 [82] resulted in reduction or repression of metastatic potential and invasiveness of various cancer types, including mCRPC and cervical cancer. The most prominent target in the list (Table 3) (as far as PrCa is concerned) is AR (androgen receptor).…”
Section: Many Of the Identified Metastasis-specific Genes Have Available Inhibitorsmentioning
confidence: 99%